Imagination and Dwelling in The House that Jack Built - Drapało, Kamila (Text Matters: A Journal of Literature, Theory and Culture, 2024)
This article employs a phenomenological and hermeneutic lens to examine the themes of dwelling, creative imagination, and the interplay between ethics and aesthetics within Lars von Trier’s film, The House that Jack Built. The film follows Jack, an engineer and self-taught architect, who pursues his dream of building an ideal home while committing morally reprehensible acts (murders). He documents these crimes using negative photography, turning them into a twisted form of artistic expression. This study explores the convergence and divergence of ethics and aesthetics, drawing on a hermeneutic understanding of imagination and dwelling. It uncovers that creative imagination holds the potential for ultimate hybris, meaning transgression and rebellion against “the great Architect behind it all.” It is a force that supplements human limitations and positions them as original, autonomous creators incapable of dwelling in a shared world. While creative imagination emerges as a force that transcends human limitations, it is also intricately linked to dwelling. It serves as a conduit for personal expression and the ability to bestow and create meaning. It becomes a prerequisite for personal identity, responsibility, and freedom. It is inherently ethical as it facilitates effective communication and the cultivation of praxis within the community. This ethical dimension is disclosed in praxis and culminates there, highlighting creative imagination as an essential human capability that enables care and dwelling.